Reading Swift's poetry - Cook, Daniel 1981- (Cambridge University Press, 2020)
Poets are makers, etymologically speaking. In practice, they are also thieves. Over a long career, from the early 1690s to the late 1730s, Jonathan Swift thrived on a creative tension between original poetry-making and the filching of familiar material from the poetic archive. The most extensive study of Swift's verse to appear in more than thirty years, Reading Swift's Poetry offers detailed readings of dozens of major poems, as well as neglected and recently recovered pieces. This book reaffirms Swift's prominence in competing literary traditions as diverse as the pastoral and the political, the metaphysical and the satirical, and demonstrates the persistence of unlikely literary tropes across his multifaceted career. Daniel Cook also considers the audacious ways in which Swift engages with Juvenal's satires, Horace's epistles, Milton's epics, Cowley's odes, and an astonishing array of other canonical and forgotten writers
Title from publisher's bibliographic system (viewed on 12 Aug 2020)
Keywords: Swift, Jonathan / 1667-1745 / Poetic works; Swift, Jonathan / 1667-1745 / Criticism and interpretation; Swift, Jonathan -- 1667-1745; Lyrik